Association between haematological parameters and outcomes following transcatheter aortic valve implantation at mid-term follow-up. Issue 2 (13th December 2022) - Abushouk, Abdelrahman; Agrawal, Ankit; Hariri, Essa; Dykun, Iryna; Kansara, Tikal; Saad, Anas; Abdelfattah, Omar; Badwan, Osamah; Jaggi, Connor; Farwati, Medhat; Harb, Serge C; Puri, Rishi; et al.
Abstract : Background: Patients undergoing transcatheter aortic valve implantation (TAVI) often have multiple comorbidities, such as anaemia and chronic inflammatory disorders. We sought to investigate the association between preoperative and postoperative haematological parameters and clinical outcomes in TAVI patients at mid-term follow-up. Methods: In the present study, consecutive patients (N=908) who underwent TAVI at the Cleveland Clinic between 2017 and 2019 with available complete blood counts were studied. Data were collected on preoperative and postoperative anaemia and elevations in neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). Survival analysis was used to study the association of haematologic parameters with all-cause mortality and major adverse cardiac and cerebrovascular events (MACCE). Results: We found that preoperative anaemia and elevated NLR were significantly associated with a higher risk of all-cause mortality (aHR=1.6 (95% CI: 1.1 to 2.0) and 1.4 (95% CI: 1.1 to 1.6), respectively) and MACCE (aHR=1.9 (95% CI: 1.3 to 2.8) and 1.6 (95% CI: 1.1 to 2.4), respectively). While an elevated preoperative PLR was not associated with increased mortality risk, it had a significant association with MACCE risk (aHR: 1.6 (95% CI: 1.1 to 2.4)). Further, postoperative anaemia, elevated NLR and PLR were associated with increased risks of all-cause mortality and MACCE. Conclusion: Pathological alterations in haematological parameters were associated with higher risks of post-TAVI mortality and MACCE at mid-term follow-up. Our findings advocate for further incorporating haematological parameters in the preoperative evaluation of TAVI candidates.